Pain and related suffering reduce attention toward others - Gonzalez Roldan, Ana Maria; Bustan, Smadar; Kamping, Sandra; Flor, Herta; Anton, Fernand (Pain practice, 2023)
Background It has been proposed that the expression of pain-related suffering may lead to an enhanced focus on oneself and reduced attention toward the external world. This study aimed at investigating whether experimentally induced painrelated suffering may lead persons to withdraw into themselves, causing a reduced focus on external stimuli as reflected by impaired performance in a facial recognition task and heightened perception of internal stimuli measured by interoceptive awareness. Methods Thirty-two participants had to recognize different emotional facial expressions (neutral, sad, angry, happy), or neutral geometrical figures under conditions of no pain, low, and high prolonged pain intensities. Interoceptive accuracy was measured using a heartbeat-detection task prior to and following the pain protocol. Results Males but not females were slower to recognize facial expressions under the condition of high painful stimulation compared to the condition of no pain. In both, male and female participants, the difficulty in recognizing another person's emotions from a facial expression was directly related to the level of suffering and unpleasantness experienced during pain. Interoceptive accuracy was higher after the pain experiment. However, neither the initial interoceptive accuracy nor the change were significantly related to the pain ratings. Conclusions Our results suggest that long-lasting and intense painful stimuli, which induce suffering, lead to attentional shifts leading to withdrawal from others. These findings contribute to a better understanding of the social dynamics of pain and pain-related suffering.